Efficacy and Safety of Placebo During the Maintenance Therapy of Ovarian Cancer in Randomized Controlled Trials: A Systematic Review and Meta-analysis - Wang, Jin-feng; Zhao, Lan-bo; Bin, Ya-di; Zhang, Kai-lu; Sun, Chao; Wang, Yi-ran; Feng, Xue; Ji, Jing; He, Li-song; Chen, Fang-yao; Li, Qi-ling (Frontiers in Oncology, 2022)
Introduction This meta-analysis evaluated the efficacy and safety of placebo during the maintenance therapy of ovarian cancer (OC) patients in randomized controlled trials (RCTs). Methods A comprehensive literature review was performed for RCTs published up to and including August 2020 from four electronic databases. We analyzed the efficacy and safety in the control arms of the maintenance therapy in advanced OC patients. Hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs) of progression-free survival (PFS) and overall survival (OS) were estimated in the placebo arms and the observation arms, respectively, using the Frequency Framework method. We also calculated the incidences of common adverse effects (AEs) in the placebo arms. Results In total, 41 articles with 20,099 (4,787 in the placebo arms, 3,420 in the observation arms, and 11,892 in the experiment arms) patients were included in this meta-analysis. Compared with observation, placebo did not improve or reduce PFS (HR, 1.02; 95% CI, 0.87–1.20; P = 0.81) and OS (HR, 1.02; 95% CI, 0.89–1.16; P = 0.76) of OC patients, while other treatments, except for radiotherapy, significantly improved PFS and OS (all P < 0.05). The incidences of AEs produced by placebo were 94.03% in all grades and 20.22% in grade ≥3. The incidences of AEs were 29.75% in fatigue, 26.38% in nausea, 24.34% in abdominal pain, 18.92% in constipation, 16.65% in diarrhea, 14.55% in vomiting, 13.89% in hypertension, and 13.14% in headache. Conclusions Placebo did not improve or reduce the PFS and OS benefits of OC patients in RCTs but increased the incidences of AEs.